High performance work system and transformational leadership: Revisiting and questioning their implications for health-related wellbeing - Ehrnrooth, Mats; Koveshnikov, Alexei; Wechtler, Heidi; Hauff, Sven (Frontiers in Psychology, 2023)
Employee well-being represents a profound management challenge for both leaders and HR professionals, and both transformational leadership (TL) and high performance work system (HPWS) are assumed to play important roles in tackling this challenge. However, we know little about their unique and relative importance in promoting well-being. To shed light on this methodologically, theoretically and practically important issue, we draw mainly on leadership substitutes theory. Based on a comprehensive mediation model we examine whether HPWS substitutes the assumed relationships between TL and employee emotional exhaustion. Our study answers to three important calls for research: to examine the joint effects of leadership and HPWS, to examine their health-related impact, and to pursue more theory contesting research in management studies. Based on data from 308 white collar employees working under 76 middle-managers in five Finnish organizations our study points to the incompleteness of previous siloed research on both TL and HPWS, sheds new light on their relationships with well-being, and suggests ways to develop both TL and HPWS theory, thus providing important guidance for future research on their effects.